2007 Sixth Mexican International Conference on Artificial Intelligence, Special Session (MICAI) 2007
DOI: 10.1109/micai.2007.32
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Morphological Feature Extraction and Support Vector Machines in Computerized ECG Interpretation

Abstract: This paper presents a novel approach that recognizing heart rhythm with the combination of adaptive Hermite decomposition and support vector machines (SVM) classification. The novelty lies in two aspects. In the first aspect, for the goal of feature extraction, the orthogonal transformation based on Hermite basis functions is proposed to characterize the morphological features of ECG data. In the other aspect, as to the multi-class electrocardiogram (ECG) classification, the one-against-all strategy is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…The investigators are concerned with the methods and techniques by which those physiological signals may be related to their annotations automatically. In this regard, a good many of computational methods, including template matching and statistical analysis in hard computing Gerencsér et al, 2002), Artificial Neural Networks (ANNs) and Fuzzy Logics (FL) in soft computing (Suzuki 1995;Tatara & Gnar 2002;Lei et al, 2008), have been proposed and validated for computerized physiological signal interpretation. In general, those techniques do not simply resort to the empirical thresholds of amplitudes and rhythms any more.…”
Section: Adaptive Clustering and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators are concerned with the methods and techniques by which those physiological signals may be related to their annotations automatically. In this regard, a good many of computational methods, including template matching and statistical analysis in hard computing Gerencsér et al, 2002), Artificial Neural Networks (ANNs) and Fuzzy Logics (FL) in soft computing (Suzuki 1995;Tatara & Gnar 2002;Lei et al, 2008), have been proposed and validated for computerized physiological signal interpretation. In general, those techniques do not simply resort to the empirical thresholds of amplitudes and rhythms any more.…”
Section: Adaptive Clustering and Classificationmentioning
confidence: 99%
“…As a consequence, the techniques of self-organizing and data clustering receive much attention in computational intelligence. A variety of them, including fuzzy c-means (FCM) (Lei et al, 2008) and self-organizing maps (SOM) (Lagerholm et al, 2000), have been extensively investigated for physiological signal analysis. By them it is possible to fuse the advantages of wavelet analysis and computational intelligence for self-organizing physiological signals.…”
Section: Adaptive Clustering and Classificationmentioning
confidence: 99%
“…Then, the test data are adopted to demonstrate the classification system. What is worthy of attention is that most of the methods of obtaining the eigenvalue integrate the RR interval length with other types of eigenvalue, such as the formal eigenvalue based on wavelet transformation, (2,3) the coefficient based on the Hermite function, (4) and the eigenvalue directly obtained from the time and frequency domains of ECG. The classification methods include the linear discrimination classification, (5,6) the support vector machine, (7,8) the artificial neural network (ANN), (9,10) and the fuzzy theory.…”
Section: Introductionmentioning
confidence: 99%
“…Actual IC-LM324 and Internal Pin. The Lorenz chaos system adopted in this study is shown in Eqs (4). and(5).…”
mentioning
confidence: 99%
“…Lots of machine learning algorithms were utilized for heartbeat classification, such as linear discrimination analysis [3], decision tree [13], artificial neural network [6,14,15], support vector machine [16,17], etc. Neural network is widely used for its simple structure, fast classification speed and high classification accuracy.…”
Section: Introductionmentioning
confidence: 99%